Efficiency Improvement of Three-Phase Cascaded H-Bridge Multilevel Inverters for Photovoltaic Systems - Nuntawat Thitichaiworakorn; Nattapon Chayopitak; Natchpong Hatti (International Journal of Photoenergy)
Medium-scale photovoltaic (PV) systems using cascaded H-bridge multilevel inverters have a capability to perform individual maximum power point tracking (MPPT) for each PV panel or each small group of panels, resulting in minimization of both power losses from panel mismatch and effect of partial shading. They also provide high power quality, modularity, and possibility of eliminating dc-dc boost stage and line-frequency transformer. However, each PV panel in the system is subjected to a double-line-frequency voltage ripple at the dc-link which reduces the MPPT efficiency. This paper proposes a dc-link voltage ripple reduction by third-harmonic zero-sequence voltage injection for improving the MPPT efficiency. Moreover, a control method to achieve individual MPPT control of each inverter cell is also presented. The validity and effectiveness of the proposed methods were verified by computer simulation.